Effects of a fixed dietary intake on changes in red blood cell delta-aminolevulinate dehydratase activity and hemolysis - Ishizaki, S.; Koshimizu, T.; Yanagisawa, K.; Akiyama, Y.; Mekada, Y.; Shiozawa, N.; Takahashi, N.; Yamakawa, J.; Kawano, Y. (International Journal of Sport Nutrition and Exercise Metabolism, 2006)
This study was to assess the effect of a fixed dietary intake on biomarkers of red blood cell (RBC) biosynthesis and degradation. Over a two-year period, eight collegiate rhythmic gymnasts participated in this study. During the first year, they ate self-selected diets. During the second year, a fixed dietary intake involving consumption of common Japanese foods containing 15 mg iron and 1500 kcal energy was maintained for 4 wk at the beginning of the program. Fixed dietary intakes resulted in significantly increased intakes of protein, minerals and vitamins, and significantly decreased fat intake, but total energy and carbohydrate intakes were unchanged. Mean values of RBC, Hb, Ht, or TIBC were not affected by the intervention. A fixed dietary intervention appeared to enhance RBC turnover by increasing the capacity for erythrocyte biosynthesis and degradation, although the prevalence of iron-deficiency anemia remained unchanged.